2014
DOI: 10.1093/jjco/hyt230
|View full text |Cite
|
Sign up to set email alerts
|

Development of Nomogram to Non-steroidal Antiandrogen Sequential Alternation in Prostate Cancer for Predictive Model

Abstract: Objectives: To clarify clinical predictors for a prostate-specific antigen decrease 50% in response to alternative non-steroidal antiandrogen therapy and to develop a nomogram to predict the prostate-specific antigen decrease 50% in response to alternative non-steroidal antiandrogen therapy in patients with advanced prostate cancer that relapsed after initial combined androgen blockade. We previously reported that combined androgen blockade with an alternative non-steroidal antiandrogen is effective for advanc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 24 publications
1
5
0
Order By: Relevance
“…The previous studies on flutamide as AAT revealed that the responders, whose PSA decline was >50% from baseline, had better prognosis and achieved sufficient benefits from flutamide [4,5,7,8]. PSA nadir and duration of sensitivity to CAB therapy are predictors of the AAT response [9,22]. Responders to flutamide in this study had statistically lower PSA nadir and longer time to PSA nadir at CAB therapy than did non-responders.…”
Section: Discussionsupporting
confidence: 48%
“…The previous studies on flutamide as AAT revealed that the responders, whose PSA decline was >50% from baseline, had better prognosis and achieved sufficient benefits from flutamide [4,5,7,8]. PSA nadir and duration of sensitivity to CAB therapy are predictors of the AAT response [9,22]. Responders to flutamide in this study had statistically lower PSA nadir and longer time to PSA nadir at CAB therapy than did non-responders.…”
Section: Discussionsupporting
confidence: 48%
“…Furthermore, although hormonal treatments have been the mainstay of treatment in advanced prostate cancer, recent data suggest potential development of cross-resistance after multiple lines of hormonal therapy [ 21 , 22 ]. In the first-in-man enzalutamide phase I/II study in patients in the United States, the rate of PSA decline of ≥50 % was significantly lower in patients with previous ketoconazole treatment versus those without [37 % (95 % CI 25–50 %) versus 71 % (95 % CI 60–81 %; p = 0.0007)] [ 19 ].…”
Section: Discussionmentioning
confidence: 99%
“…The remaining 13 studies were identified with an overall high RoB [18] , [22] , [23] , [28] , [29] , [30] , [31] , [32] , [33] , [34] , [35] , [36] , [37] . Eight of these studies were validated internally or externally.…”
Section: Resultsmentioning
confidence: 99%
“…Additionally, predictive models can identify which patients are likely to experience adverse events or toxicity from a given treatment based on their clinical characteristics, amongst other factors. This provides useful information for the decision-making process between clinicians and patients when selecting treatment [18] .…”
Section: Introductionmentioning
confidence: 99%